2013
DOI: 10.3121/cmr.2013.1130
|View full text |Cite
|
Sign up to set email alerts
|

Does CALU SNP rs1043550 Contribute Variability to Therapeutic Warfarin Dosing Requirements?

Abstract: Objectives: Calumenin, a molecular chaperone, exerts a regulatory effect on the vitamin K-dependent γ-carboxylation redox cycle that inhibits transfer of the reduced vitamin K from VKORC1, the pharmacological target of warfarin, to the γ-carboxylase. Because of its polymorphic structure and central role in the warfarin metabolic pathway, a contributory role for calumenin to warfarin dose variability has been posited. The current study sought to validate modulation of therapeutic dosing requirements by a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
(45 reference statements)
0
5
0
1
Order By: Relevance
“…[1][2][3][4][5] Genetic variations in cytochrome P450-4F2 (CYP4F2), g-glutamyl carboxylase (GGCX), epoxide hydrolase 1 (EPHX1), calumenin (Calu), factor IX (F9), and factor VII (F7) gene also have shown subsidiary association with warfarin response. [6][7][8][9][10][11][12] Other nongenetic factors including ethnicity, age, body mass index, weight, and gender are also known to have a minor role in warfarin sensitivity. [13][14][15][16][17][18][19] Based on pharmacogenetics, clinical, and demographic factors, population-based warfarin pharmacogenomic algorithms have been generated for various ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Genetic variations in cytochrome P450-4F2 (CYP4F2), g-glutamyl carboxylase (GGCX), epoxide hydrolase 1 (EPHX1), calumenin (Calu), factor IX (F9), and factor VII (F7) gene also have shown subsidiary association with warfarin response. [6][7][8][9][10][11][12] Other nongenetic factors including ethnicity, age, body mass index, weight, and gender are also known to have a minor role in warfarin sensitivity. [13][14][15][16][17][18][19] Based on pharmacogenetics, clinical, and demographic factors, population-based warfarin pharmacogenomic algorithms have been generated for various ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Fluctuations of individual warfarin dosages can influence the severity of RHD in genetic factors. At present, researches showed usage of warfarin on stable doses on RHD causing CYP2C9 , CYP4F2 and VKORC1 gene polymorphisms in the Chinese Han population [31,32]. In our study, the long-term anticoagulant therapy of warfarin in RHD patients after valve replacement changed expression levels of BNP DNA methylation sites in the field of apparent genetics.…”
Section: Discussionmentioning
confidence: 54%
“…[59][60][61] A number of other studies have also shown such deviation from HWE without affecting the results. 6,12,[62][63][64] As far as the status of LD among these SNPs is concerned, a recent Italian study also reported nonexistence of LD between VKORC1 1173C>T and VKORC1-1639G>A genotypes. 10 A number of studies have revealed that different VKORC1 SNPs group differently to form haplotypes because of diverse LD relationship in different populations and their distribution varies in different populations.…”
Section: Discussionmentioning
confidence: 99%